2016
DOI: 10.1002/jcla.22054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Hemochromatosis Mutations on Iron Overload among the Indian β Thalassemia Carriers

Abstract: This suggests that iron load in BTT tends to aggravated with the co-inheritance of the H63D mutation. The mutant H63D gene showed the presence of haplotype 6 which is reported in the European population suggesting a common origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[ 37 ] Some studies have indicated that the common mutation of the HFE gene (C282Y) causes a common type of hereditary hemochromatosis. [ 38 ] The H63D variant, a common polymorphism in the HFE gene, appears to modulate iron absorption. β-thalassemia carriers who are homozygous for the HFE H63D variant have higher serum ferritin levels than carriers without the variant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 37 ] Some studies have indicated that the common mutation of the HFE gene (C282Y) causes a common type of hereditary hemochromatosis. [ 38 ] The H63D variant, a common polymorphism in the HFE gene, appears to modulate iron absorption. β-thalassemia carriers who are homozygous for the HFE H63D variant have higher serum ferritin levels than carriers without the variant.…”
Section: Resultsmentioning
confidence: 99%
“…Several genes implicated in iron homeostasis have been characterized, including those encoding homeostatic iron regulators (HFE), transferrin receptor 2, ferroportin, hepcidin, and hemojuvelin [37] . Some studies have indicated that the common mutation of the HFE gene (C282Y) causes a common type of hereditary hemochromatosis [38] . The H63D variant, a common polymorphism in the HFE gene, appears to modulate iron absorption.…”
Section: Resultsmentioning
confidence: 99%
“…The role of H63D mutation polymorphism in β-thal major or carrier conditions has been studied in regions with a high incidence of H63D, such as in Southern Europe and Asia. Various studies have yielded conflicting conclusions (shown in Table 1): some studies from Italy, Portugal, India and Egypt suggested that iron overload might arise from the interacting effect of β-thal with homozygous or even heterozygous H 63 D mutations (13,(19)(20)(21)(22)(23); other reports from Italy, India, Thailand, Brazil and Spain indicated that the iron status was not related to the H63D mutation status (24)(25)(26)(27)(28)(29). The discrepancy may be due to the sample size, hereditary background variations in different racial populations, the sex ratio and the severity of thalassemia.…”
Section: Discussionmentioning
confidence: 99%